Pharmacokinetics, Safety, and Efficacy of Glecaprevir/Pibrentasvir in Children With Chronic HCV: Part 2 of the DORA Study. Issue 1 (23rd July 2021) - Jonas, Maureen M.; Rhee, Susan; Kelly, Deirdre A.; Del Valle‐Segarra, Antonio; Feiterna‐Sperling, Cornelia; Gilmour, Susan; Gonzalez‐Peralta, Regino P.; Hierro, Loreto; Leung, Daniel H.; Ling, Simon C.; Lobzin, Yuri; Lobritto, Steven; et al.
Abstract : Background and Aims: Glecaprevir/pibrentasvir (GLE/PIB) has shown high efficacy and safety in chronic HCV‐infected adults and adolescents; data in children were limited. DORA part 2 is a phase 2/3, nonrandomized, open‐label study evaluating the pharmacokinetics, efficacy, and safety of a pediatric formulation of GLE and PIB in children ages 3 to < 12 years. Approach and Results: Children with chronic HCV infection, genotype 1‐6, with or without compensated cirrhosis, were divided into three cohorts by age—cohort 2 (9 to < 12 years), cohort 3 (6 to < 9 years), and cohort 4 (3 to < 6 years)—and given weight‐based doses of GLE and PIB for 8, 12, or 16 weeks. Primary endpoints were sustained virologic response at posttreatment week 12 (SVR12) and steady‐state exposure; secondary endpoints were rates of persistent viremia, relapse, and reinfection. Safety and laboratory abnormalities were assessed. Final pediatric dosages determined to be efficacious were 250 mg GLE + 100 mg PIB (in children weighing ≥ 30 to < 45 kg), 200 mg GLE + 80 mg PIB (≥ 20 to < 30 kg), and 150 mg GLE + 60 mg PIB (12 to < 20 kg). Of 80 participants enrolled and dosed, 96% (77/80) achieved SVR12. One participant, on the initial dose ratio, relapsed by posttreatment week 4; no participants had virologic failures on the final dose ratio of GLE 50 mg/PIB 20 mg. Two nonresponders prematurely discontinued the study. Most adverse events (AEs) were mild; no drug‐related serious AEs occurred. Pharmacokinetic exposures were comparable to those of adults. Conclusions: A pediatric formulation of GLE/PIB was highly efficacious and well tolerated in chronic HCV‐infected children 3 to < 12 years old.